Plant Growth-Promoting Rhizobacteria With ACC Deaminase Activity Enhance Maternal Lateral Root and Seedling Growth in Switchgrass - Chen, Zhao; Zhou, Wennan; Sui, Xin; Xu, Nan; Zhao, Tian; Guo, Zhipeng; Niu, Junpeng; Wang, Quanzhen (Frontiers in Plant Science, 2022)
Switchgrass, C4 plant with high potential as a bioenergy source, is unsteady in yield under sub-optimal conditions. Bacteria containing ACC (1-aminocyclopropane-1-carboxylate synthase) deaminase can promote plant growth. We isolated bacteria containing ACC deaminase activity from switchgrass rhizosphere using an orthogonal matrix experimental design with four factors (bacterial liquid concentration, bacterial liquid treatment time, nitrogen content and NaCl) to quantitatively investigate the effects and pairwise interactions on the seedling growth. Pseudomonas sp. Y1, isolated from the switchgrass cv. Blackwell rhizomes was selected. We optimized the inoculation bacterial concentration, treatment time, NaCl and nitrogen concentration for the seedling growth. The optimal bacterial concentration, treatment time, NaCl and nitrogen content was 0.5 - 1.25 OD at 600 nm, 3 h, 60 - 125 mM and 158 mg L-1, respectively. Pseudomonas sp. Y1 significantly increased the total root length (TRL), root surface (RS), shoot length (SL), and fresh and dry weight (FW and DW, respectively) through an effective proliferation of the number of first-order lateral roots (NFL) and root tips (NRT). Indicating that Pseudomonas sp. Y1 has a higher potential to be used as plant growth-promoting rhizobacteria (PGPR) bacteria.